Smoking cessation and weight change in relation to cardiovascular disease incidence and mortality among patients with type 2 diabetes: a population-based cohort study - Liu, Gang (Lancet Diabetes Endocrinol, 2020)
BACKGROUND: Smoking cessation is especially critical for smokers with diabetes to reduce their overall markedly elevated risk of cardiovascular disease (CVD) and premature mortality, although the role of weight change in the long-term health consequence of smoking cessation remains to be characterized. This study aimed to examine smoking cessation and subsequent weight change in relation to incident cardiovascular events and all-cause and cause-specific mortality among adults with diabetes. METHODS: This prospective analysis included 10,809 men and women with diabetes, who were either current smokers or never smokers without CVD or cancer at diabetes diagnosis. Information on demographics, newly diagnosed diseases, medical history, and lifestyle factors, including smoking status and weight change, was updated every two years through validated questionnaires. FINDINGS: During 153,166 and 152,811 person-years of follow-up, 2,580 incident cases of CVD and 3,827 deaths occurred among participants with diabetes. Compared with those who continued to smoke, recent quitters (2–6 consecutive years since smoking cessation) without weight gain within the first 6 years of quitting had a significantly lower risk of CVD and CHD. The multivariate-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for CVD were 0.83 (0.70–0.99) among all recent quitters, 0.77 (0.62–0.95) among recent quitters without weight gain, 0.99 (0.70–1.41) among recent quitters with weight gain of 0.1 to 5.0 kg, 0.89 (0.65–1.23) among recent quitters with weight gain of more than 5.0 kg, and 0.72 (0.61–0.84) among longer-term quitters (>6 consecutive years since smoking cessation). In addition, weight gain within 6 years following smoking cessation did not attenuate the inverse relationship between long-term quitting and mortality among diabetes patients. The multivariate-adjusted HRs (95% CIs) for mortality were 0.69 (0.58–0.82) among long-term quitters without weight gain within 6 years following cessation, 0.57 (0.45–0.71) among long-term quitters with weight gain of 0.1 to 5.0 kg, and 0.51 (0.42–0.62) among long-term quitters with weight gain of more than 5.0 kg. Similar results were observed for CVD and cancer mortality. INTERPRETATION: Smoking cessation without subsequent weight gain is significantly associated with a lower CVD incidence and mortality among smokers with diabetes. Weight gain following smoking cessation attenuates the reductions in the risk of developing CVD, but not premature death, among diabetic smokers who quit smoking.